2009
DOI: 10.1007/s12519-009-0022-5
|View full text |Cite|
|
Sign up to set email alerts
|

Postoperative sepsis in infants below 6 months of age

Abstract: Postoperative sepsis syndrome is a frequent complication in infants below 6 months of age and causes significant prolongation of hospital stay. Adequate prevention and therapeutic strategies warrant further prospective investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
0
14
1
2
Order By: Relevance
“…In their single‐centre study of patients < 6 months who underwent abdominal and thoracic operations, Kessler et al observed a 6.9% sepsis rate. They identified young postnatal age, prolonged surgical time, the presence of a central venous catheter and pre‐operative antibiotic treatment as risk factors for sepsis . In our study, no significant differences were observed between the CEGA and GA groups, with respect to patient age, weight, surgical time, or duration of central venous catheters.…”
Section: Discussioncontrasting
confidence: 50%
“…In their single‐centre study of patients < 6 months who underwent abdominal and thoracic operations, Kessler et al observed a 6.9% sepsis rate. They identified young postnatal age, prolonged surgical time, the presence of a central venous catheter and pre‐operative antibiotic treatment as risk factors for sepsis . In our study, no significant differences were observed between the CEGA and GA groups, with respect to patient age, weight, surgical time, or duration of central venous catheters.…”
Section: Discussioncontrasting
confidence: 50%
“…In addition, the types of surgical interventions usually performed in neonates are also clearly distinct. More recently, Kessler reported a rate of post-operative sepsis of 6.9 % in a smaller cohort of infants of less than 6 months of age admitted to a tertiary care pediatric institution in Switzerland (n = 260) [19]. In this latter study a low gestation, certain types of surgeries as well as a prolonged operative time were associated with an increased rate of post-operative infection, although only the most severe cases of sepsis were included [19].…”
Section: Discussionmentioning
confidence: 94%
“…More recently, Kessler reported a rate of post-operative sepsis of 6.9 % in a smaller cohort of infants of less than 6 months of age admitted to a tertiary care pediatric institution in Switzerland (n = 260) [19]. In this latter study a low gestation, certain types of surgeries as well as a prolonged operative time were associated with an increased rate of post-operative infection, although only the most severe cases of sepsis were included [19]. Only a minority of infants with SSI presented a positive blood culture in our study, which emphasizes the importance of considering all infant with a clinical diagnosis of SSI regardless of blood culture results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Based on a review of the epidemiology of sepsis in the United States (high rates in winter, low rates in summer, high rates in the northeast, low rates in the west, [3] higher rates for African-Americans than white Americans, and comorbid diseases linked to low serum 25-hydroxyvitmin D [25(OH)D]), it was hypothesized that higher serum 25(OH)D levels could reduce the risk of sepsis. As the design of the reported study [1] was observational and retrospective, conclusions on preventive strategies can only be drawn with caution. [5] Thus, it would be worthwhile supplementing infants preparing for surgery with vitamin D to bring their serum 25(OH)D levels above 40 ng/mL (100 nmol/L), the level that has generally been found associated with optimal health.…”
Section: Vitamin D Supplementation Could Reduce Risk Of Sepsis In Infmentioning
confidence: 99%